PENGARUH BUDAYA PERUSAHAAN TERHADAP KEUNGGULAN BERSAING MELALUI KEPUASAN KARYAWAN PADA PERUSAHAAN KAFE RESTORAN DI SURABAYA - Angel, Caroline (Business Accounting Review, 2015)
This study aimed to examine the affect of corporate culture to competitive advantage through employeesâ satisfaction at cafe restaurant companies in Surabaya . Data used in this study were primary data. The sample used in this study were 30 cafe restaurant company in Surabaya with purposive sampling method. The hypotheses in this study analyzed by using structural equation model (SEM) with SmartPLS 2.0. The result revealed that, corporate cultureÂ  significantly affect competitive advantage directly, and indirectly through intervening variables which were employeesâ satisfaction.